ASSESSMENT OF TECHNICAL CHANGES DURING SWIMMING PERFORMANCE IN TRAINED JUNIOR SWIMMERS. Issue 17 (24th October 2013) - Archer, DT; Berry, L; Dixon, S; Hogg, R
Abstract : Inertial sensor technology is a reliable technique to provide measures such as acceleration and deceleration in laboratory and field conditions (Boyd et al . IJSPP 2011;6:311–321). In competitive pool swimming, the athlete's goal is to adopt an efficient technique to maximise propulsion and minimise drag and deceleration (Barbosa et al . JSMS 2010;13:262–269). The aim of the present study was to assess technical aspects of swimming performance using the inertial sensors contained within a team sports GPS system. Nine regional and national level swimmers, three male and six females aged 13±3 years, height 1.63±0.74 m and body mass 56.5±10.0 kg performed three maximal 800-m freestyle time trials on three occasions in a 25 m pool, each separated by seven days. Following a 400-m standardised warm up, swimmers started the time trial with a push off from the wall. A tri-axial accelerometer and gyroscope, contained within the Catapult Minimax S4 Athlete Monitoring System was used to assess split times, Player Load, stroke rate and rate of body roll at 100 Hz. Subject's mean 800-m time was 727.8±27.2 s and did not differ between trials, resulting in a coefficient of variation (CV) of 3±1% between races. The greatest swim velocities occurred in the initial 25 m in each trial. Player Load was greatest and the rate of body roll tended to be lowest on this lap. Mean Player Load per stroke, stroke rate and rate of body roll did not differ between trials (P>0.05) and mean CV values varied between 4 and 7% across the 32 laps, indicating low between-lap variability for these parametersTable 1 . In conclusion, the Catapult Minimax S4 system can be used to collect technical data during swim performance, providing measures of within- and between- lap and race variability.